1998
DOI: 10.1111/j.1472-8206.1998.tb00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial hemodynamic effects of nicorandil in a canine model of acute congestive heart failure: Comparison with nitroglycerin and cromakalim

Abstract: Comparative hemodynamic effects of nicorandil (NCR), nitroglycerin (NTG) and cromakalim (CRM) were examined in a canine model of acute congestive heart failure (CHF). CHF was produced by injections of saponin into coronary arteries of anesthetized dogs followed by volume loading and continuous i.v. infusion of methoxamine. After the treatment, aortic blood flow (AoF), left ventricular dP/dt and myocardial segment shortening (SS) markedly decreased, while the left ventricular end-diastolic pressure (LVEDP), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…Furthermore, in the canine acute congestive heart failure model, nicorandil may exert beneficial hemodynamic effects mainly due to decrease in both afterload and preload rather than the coronary vasodilator effect [7]. The present result in the adult rat heart, however, revealed that nicorandil increased preload (EDV) without any effects on afterload (Ea and ESP ESV ).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Furthermore, in the canine acute congestive heart failure model, nicorandil may exert beneficial hemodynamic effects mainly due to decrease in both afterload and preload rather than the coronary vasodilator effect [7]. The present result in the adult rat heart, however, revealed that nicorandil increased preload (EDV) without any effects on afterload (Ea and ESP ESV ).…”
Section: Discussioncontrasting
confidence: 65%
“…It was actually reported that at high concentrations nicorandil exerted negative inotropic effects on human left ventricular papillary muscles predominantly by opening the K ATP channels [5]. In acute ischemic and congestive heart failure canine models, nicorandil was considered to improve cardiac contractility due to the reduction of both preload and afterload mediated by K ATP channel opening actions with NO-like actions [6,7]. No positive inotropic effects of nicorandil on the normal heart model, however, have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, nicorandil increases coronary blood flow, reduces preload and afterload, and exerts an antianginal action [1], [2]. In addition, beneficial hemodynamic effects of nicorandil have also been demonstrated in acute HF, suggesting a possible effect of this drug in the treatment of HF [3]. In fact, intravenous administration of nicorandil attenuated exercise-induced LV diastolic dysfunction in individuals with hypertrophic cardiomyopathy, probably as a result of its beneficial effect on abnormal coronary microcirculation [4].…”
Section: Introductionmentioning
confidence: 99%